ex turpi causa - Black, Henry Campbell (Black's law dictionary, 2019)
For more than a century, Black's Law Dictionary has been the gold standard for the language of law. This edition contains more than 50,000 terms, including more than 7,500 terms new to this edition. It also features expanded bibliographic coverage, definitions of more than 1,000 law-related abbreviations and acronyms, and reviewed and edited Latin maxims